Menguak Nilai Kearifan Lokal di Balik Praktik Akuntansi Biaya oleh Para Petani: Studi Etnometodologi Islam - Mohamad Anwar Thalib; Fathir Paputungan; Muhliansyah J.A. Kuntuamas (Media Bisnis, 2023)
This research departs from problems related to the study of cost accounting in the agricultural context, which only reveals the reality of accounting limited to the material and ignores local cultural and spiritual values. This study aims to reveal the value of local wisdom behind agricultural accounting practices. This study uses an Islamic paradigm with an Islamic ethnomethodological approach. There are five data analysis stages: charity, knowledge, faith, revelation information, and courtesy. The results showed that there were agricultural cost accounting practices in the form of rental fees for agricultural land expansion services, planting rice seeds, costs for seeds, fertilizers, and pesticides, as well as increased costs due to rising fuel prices. Financial accounting practice is conditional on the value of patience (patience). The value of patience is reflected through the actions of farmers who persist in this profession, even though the cost of managing agricultural land is increasing due to rising fuel prices. In Gorontalo's Islamic culture, elders often instill the value of patience in the local community through the expression (lumadu) “mopo’o tanggalo duhelo” This expression means full of patience. The implication of this research is to present agricultural accounting practices based on local cultural values.